LIGHTING DESIGN IMPROVEMENT FOR ENHANCING INDOOR VISUAL QUALITY OF GPIB IMMANUEL CHURCH MALANG - Dinapradipta, Asri; N. Ekasiwi, Sri Nastiti; Sudarma, Erwin; Defiana, Ima; Erwindi, Collinthia; Krisdianto, Johanes; Noerwasito, Vincentius Totok (Universitas Sebelas Maret Surakarta, 2018)
Lighting affects how people feel, react, and function in various settings, therefore lighting design strategy for worship room at churches should be aimed not only at fulfil the standard visual performance but should also be set as to enrich the room’s perception i.e. as the God’s holy place as well as a place for contemplation. Lighting problems found at the worship room of GPIB Immanuel Malang are not merely on the inappropriateness of lighting level and distributions, but also on the absence of the church’ nuance as a place for contemplation. This paper is intended to report a proposed schematic lighting design for improving the situation. Using visual hierarchical approach, the lighting design aspects such as intensity, colour rendering, type, direction and arrangement of luminaires are determined and integrated. The proposed lighting design strategy is expected to be able to solve luminous problems and create the designated room’s nuance/perceptions.